Historical Dictionary of Early North America - Wesson, Cameron B. (Rowman & Littlefield Publishers, 2004)
Those unfamiliar with the prehistory of North America have a general perception of the cultures of the continent that includes Native Americans living in tipis, wearing feathered headdresses and buckskin clothing, and following migratory bison herds on the Great Plains. Although these practices were part of some Native American societies, they do not adequately represent the diversity of cultural practices by the overwhelming majority of Native American peoples. Media misrepresentations shaped by television and movies along with a focus on select regions and periods in the history of the United States have produced an extremely distorted view of the indigenous inhabitants of the continent and their cultures. The indigenous populations of North America created impressive societies, engaged in trade, and had varied economic, social, and religious cultures. Over the past century, archaeological and ethnological research throughout all regions of North America has revealed much about the indigenous peoples of the continent. This book examines the long and complex history of human occupation in North America, covering its distinct culture as well as areas of the Arctic, California, Eastern Woodlands, Great Basin, Great Plains, Northwest Coast, Plateau, Southwest, and Subarctic. Complete with maps, a chronology that spans the history from 11,000 B.C. to A.D. 1850, an introductory essay, more than 700 dictionary entries, and a comprehensive bibliography, this reference is a valuable tool for scholars and students. An appendix of museums that have North American collections and a listing of archaeological sites that allow tours by the public also make this an accessible guide to the interested lay reader and high school student.